Efficacy and Safety of Minimally Invasive Surgery Versus Open Laparotomy for Interval Debulking Surgery of Advanced Ovarian Cancer After Neoadjuvant Chemotherapy: A Systematic Review and A Meta-Analysis - Zeng, Siyuan; Yu, Yongai; Cui, Yuemei; Liu, Bing; Jin, Xianyu; Li, Zhengyan; Liu, Lifeng (Frontiers in Oncology, 2022)
Abstract: Objective: The selection of minimally invasive surgery (MIS) or open laparotomy for ovarian cancer (OC) after neo-adjuvant chemotherapy still remains controversial. This study aimed to assess the efficacy and safety of MIS versus open laparotomy following neo-adjuvant chemotherapy for advanced OC, so as to provide another option to select optimal surgical procedures for OC patients. Methods: Relevant literatures about the risks of progression or mortality between women receiving MIS and open laparotomy for interval debulking surgery (IDS) were searched in the online databases, including PubMed, Embase and the Cochrane Library with the following keywords: "Ovarian Neoplasms", "Minimally Invasive Surgical Procedures", "Laparotomy", and "Neo-adjuvant therapy". Eligible studies were screened out for further meta-analysis. Results: Six eligible literatures, with 643 patients in MIS group and 2885 patients in open laparotomy group, were included in this meta-analysis. No significant differences were detected in the overall survival (OS) of OC patients who were treated with MIS or open laparotomy (HR=0.85; 95%CI = 0.59-1.23; Heterogeneity: P=0.051, I2=57.6%). However, the progression-free survival (PFS) was significantly higher in OC patients treated with MIS than those treated with laparotomy (HR=0.73; 95%CI=0.57-0.92; Heterogeneity: P=0.276, I2=22.4%). The completeness of debulking removal（R0 rate）in the open laparotomy group was not statistically higher compared with the control group (RR=1.07, 95%CI=0.93-1.23; Heterogeneity: P=0.098, I2=52.3%), and no significant differences in residual disease of ≤ 1 cm (R1) (RR=1.08, 95%CI=0.91-1.28; Heterogeneity: P=0.330, I2=12.6%) and postoperative complications were found between the two groups (RR=0.72, 95%CI=0.34-1.54; Heterogeneity: P=0.055, I2=60.6%). Furthermore, the length of stays in hospital was significantly shorter in OC patients treated with MIS than those treated with open laparotomy (SMD=-1.21, 95%CI=-1.78-0.64; Heterogeneity: P<0.001, I2=92.7%). Conclusions: For IDS after NACT in patients with advanced OC, complete cytoreductive surgery with MIS is another feasible and effective choice.Trial Registration: PROSPERO Identifier: CRD42022298519